2015
DOI: 10.1016/j.compedu.2015.03.018
|View full text |Cite
|
Sign up to set email alerts
|

The effects of computer-based games and collaboration in large groups vs. collaboration in pairs or traditional methods

Abstract: As new technologies have emerged in the last few years, the learning process has been changing. New and powerful e-learning systems are being developed and new teaching methods can be used in classrooms. In this paper, we present a computer-based game with an educational background that is played on a large-size tabletop display. The game can be used as reinforcement for educational content related to historical ages. The game uses natural interaction. A study to compare the traditional learning method with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 44 publications
1
12
0
2
Order By: Relevance
“…The results showed statistically significant improvement in knowledge that corroborate that students increase their knowledge about teeth morphology using our system. On another of our previous works, we demonstrated that the improvement in knowledge is also statistically significant when the students play in pairs and also in large groups (up to 12 children) (Martín-SanJosé et al 2015). These results are in line with previous works that have argued for the immense potential of educational computer games in helping students to improve their learning performance (e.g., Hwang and Wu 2012;Martí-Parreño, Méndez-Ibáñez, and Alonso-Arroyo 2016).…”
Section: Vr System For Dental Learningsupporting
confidence: 91%
“…The results showed statistically significant improvement in knowledge that corroborate that students increase their knowledge about teeth morphology using our system. On another of our previous works, we demonstrated that the improvement in knowledge is also statistically significant when the students play in pairs and also in large groups (up to 12 children) (Martín-SanJosé et al 2015). These results are in line with previous works that have argued for the immense potential of educational computer games in helping students to improve their learning performance (e.g., Hwang and Wu 2012;Martí-Parreño, Méndez-Ibáñez, and Alonso-Arroyo 2016).…”
Section: Vr System For Dental Learningsupporting
confidence: 91%
“…Knowledge gains that arise from collaborative efforts are valuable from the standpoint of lifelong and work-based learning (Kayes, Kayes, & Kolb, 2005) and are of particular interest to the community of Computer Supported Collaborative Learning (CSCL), which specifically examines the development of knowledge and skills as a product of collaborative activities. The analysis suggests clear advantages of LIDs over other media, with five (out of six) studies reporting positive effects (Hwang & Su, 2012;Martin-SanJose, Juan, Segui, & Garcia-Garcia, 2015;Schneider & Blikstein, 2018;Schneider et al, 2012;Shaer et al, 2011) and one study reporting no effect (Piper & Hollan, 2009). The positive effects of LIDs were shown in comparison to paper conditions (Martin-SanJose et al, 2015;Piper & Hollan, 2009;Schneider et al, 2012) and single-user environments (Hwang & Su, 2012;Shaer et al, 2011).…”
Section: Knowledge Outcomesmentioning
confidence: 96%
“…The analysis suggests clear advantages of LIDs over other media, with five (out of six) studies reporting positive effects (Hwang & Su, 2012;Martin-SanJose, Juan, Segui, & Garcia-Garcia, 2015;Schneider & Blikstein, 2018;Schneider et al, 2012;Shaer et al, 2011) and one study reporting no effect (Piper & Hollan, 2009). The positive effects of LIDs were shown in comparison to paper conditions (Martin-SanJose et al, 2015;Piper & Hollan, 2009;Schneider et al, 2012) and single-user environments (Hwang & Su, 2012;Shaer et al, 2011). One example is the study of Shaer et al (2011) who compared a LID with a PC environment in connection with the accomplishment of a knowledge task (exploring genomic information, e.g.…”
Section: Knowledge Outcomesmentioning
confidence: 96%
“…Anahtar Sözcükler: Yabancı Dil olarak İngilizce, İngilizce Öğretmen Adayları, Bilgisayar Destekli Dil Öğretimi ÖZET Amaç ve Önem: Bilgisayar Destekli Dil Öğretimi (BDDÖ) araçlarının dil öğretiminde etkililiği üzerine tartışmalar (Dunkel, 1991; Felix, 2005;Hubbard, 2003; Kern, 2006;Phipps & Merisotis, 1999) devam etse de, birçok çalışma teknolojinin öğrencilerin motivasyonunu, öğretim ve öğrenme süreçlerini olumlu yönde etkilediğini göstermektedir (Barak, Watted & Haick, 2016. Hung, 2015Martín-SanJosé, Juan, Seguí & García-García, 2015). Öğrenmeyi ve öğretim ortamlarını nasıl etkilediği sorusuna cevap olarak, teknolojinin eğitimdeki etkililiğinin nasıl ve kim tarafından kullanıldığına göre değiştiğini söyleyebiliriz.…”
unclassified
“…Hung, 2015Martín-SanJosé, Juan, Seguí & García-García, 2015). Almost a decade ago, Kern (2006) discussed the question of effectiveness of CALL tools and concluded that their effectiveness in language classes mostly depends on how technology is used in the classroom: the complexity of the issues involved in technology and language learning is pushing us to look beyond gross decontextualized measures of effectiveness to understand effectiveness in terms of the specifics of what people do with computers, how they do it, and what it means to them.…”
Section: Introductionmentioning
confidence: 99%